Analysis of advertising media in automotive dealerships in Guasave, Sinaloa, México - Lugo Hernández, Lourdes Teresa; Beltran Lugo, Lizbeth; Cuadras Berrelleza, Aldo Alan; Castro Rivera, Radamés; Moreno López, Esteban Otoniel (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This article is oriented on conducting a study of advertising media used in automotive dealerships in Guasave, Sinaloa, Mexico, to analyse the advertising media they use, the method used was mixed, with a descriptive approach, and data collection was carried out from November to December 2022. The results showed that automotive dealers increased the implementation of advertising resources through the Internet, adapting to the changes of consumers. However, they expressed that it is advisable to make a combination of both traditional and digital, to improve the massification of advertising information. The analysis obtained relevant information on the advantages and disadvantages of each advertising medium used, which supports companies in making decisions concerning media planning.